3D Visualization as A Web-Based Promotional Media (Case Study: Faculty of Engineering, University of Muhammadiyah Bengkulu) - Rahmat Hidayat; Muhammad Husni Rifqo (Jurnal Komputer, Informasi dan Teknologi, 2022)
Promotion is an activity that is commonly carried out by various universities, especially when they are about to enter a new school year to attract prospective new students. The Faculty of Engineering is one of the faculties at the University of Muhammadiyah Bengkulu. The Faculty of Engineering has a variety of promotional media, one of which is a website with the address at ft.umb.ac.id. The official website of the Faculty of Engineering provides information about achievements that have been achieved, important activities carried out by students and lecturers, profiles of the Faculty of Engineering and each study program in it, and links to related website pages. However, the website does not provide information about what is in the Faculty of Engineering. This makes website users not know how the atmosphere is when they are in the Faculty of Engineering. The research method used in the study was research and development (R&D) method. This research produces a website page that contains a 3D visualization of the Faculty of Engineering building and rooms and objects in it that can be used as additional promotional media options for the Faculty of Engineering, University of Muhammadiyah Bengkulu.